DUNIA MODE DAN BIDANG USAHA PEMBUATAN BUSANA - Tampubolon, Hotmaria (Universitas Negeri Medan, 2017)
From time to time, clothing stores sell clothing with unique cutting styles. This piece of clothing style captured the hearts of buyers, so clothing that some time before was very popular, had to be abandoned, that's the appearance of a fashion phenomenon. By